Kegiatan Penyuluhan dan Pemeriksaan Kesehatan untuk Membiasakan PHBS bagi Warga Desa Kemantren - Imam Rofiki; Siti Roziah Ria Famuji (Universitas Lancang Kuning, 2020)
Efforts to familiarize clean and healthy life is significant to improve the degree of public health. The strategies for familiarize clean and healthy living behaviors are counseling and checking of clean and healthy life behavior. The purpose of these activities was to increase knowledge, awareness, and potential of clean and healthy life behavior in Kemantren Village, Malang. This dedication involved the participation of the people of Kemantren Village so that the community could realize that health improvement can be started from healthy daily living habits. The method used was counseling, and health checking. The results of the service showed that the community gave a positive response and was very enthusiastic in participating in health education and counseling activities.